Program Corporate Social Responsibility (CSR) SENDIK BRI Stusi Kasus : Pelaksanaan CSR Sentral Pendidikan Bank Rakyat Indonesia Padang Terhadap Masyarakat Pasar Baru, Kelurahan Cupak Tangah, Kecamatan Pauh - Oktavia, Dian Anggraini (Jurnal Pelangi : Research of Education and Development, 2012)
Development of a country not just the responsibility of government alone,every human being contributes to social welfare and community enhancement.The business role is to promote healthy economic growth with environmentalconsiderations are a factor. Now the business is no longer just pay attention to thecompany's financial records alone (single bottom line), but already includes thefinancial aspects, social aspects and environmental aspects of the so-called triplebottom line. Synergy of these three key elements of the concept of sustainabledevelopment (sustainable development). patterns of partnership (partnership) withall stakeholders to play a role in development, while improving its performance inorder to continue to survive and even thrive into the compa pany that is able tocompete. These efforts can be generally referred to as corporate socialresponsibility or corporate citizenship and is intended to encourage more ethicalbusiness world in carrying out its activities so as not to influence or a negativeimpact on society and the environment, so that eventually the business will beable to survive in a sustainable manner to obtain economic benefits the main aimof the business world.